2013
DOI: 10.1080/09585192.2013.767059
|View full text |Cite
|
Sign up to set email alerts
|

Committed to the organization or the job? Effects of perceived HRM practices on employees' behavioral outcomes in the Japanese healthcare industry

Abstract: This paper attempts to document how employees' perceptions of organizations' human resource management (HRM) practices influence their work behavior and outcomes, including the level of turnover intentions and job quality improvement, in a Japanese organizational and management context. In particular, an examination was made to clarify the mediating role of person-environment (P -E) fit and multiple aspects of work commitment to reach possible explanations of the relationships between perceived HRM practices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 43 publications
8
34
1
Order By: Relevance
“…This research presents several noteworthy findings. Consistent with the rationale of the ASA framework and evidence from previous research (Boon et al, 2011;Takeuchi and Takeuchi, 2013), the findings of the current study revealed that employee perceptions of HPHRP had a significant positive relationship with P-O fit. This confirms that HPHRP communicate organizational values, goals and expectations to employees which, in turn, facilitates greater congruence between employees and organizations (Boon et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…This research presents several noteworthy findings. Consistent with the rationale of the ASA framework and evidence from previous research (Boon et al, 2011;Takeuchi and Takeuchi, 2013), the findings of the current study revealed that employee perceptions of HPHRP had a significant positive relationship with P-O fit. This confirms that HPHRP communicate organizational values, goals and expectations to employees which, in turn, facilitates greater congruence between employees and organizations (Boon et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…In fact, Boon et al (2011) found that P-O fit mediated the relationship between HPHRP and both organizational citizenship behaviours and organizational commitment in the Netherlands. Takeuchi and Takeuchi (2013) also found that P-O fit mediated the relationship between HPHRP and organizational commitment in Japan. The focus in this study, as mentioned above, will be on two negative employee outcomes: job stress and quit intentions.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations